EVALUATION OF SODIUM CITRATE ANTICOAGULANT FOR THE RESOLUTION OF EDTA-DEPENDENT PSEUDO THROMBOCYTOPENIA - Sharif, Fatima; Junaid, Ayesha; Ashraf, Khadija; Ijaz, Maira; Saeed, Maria; Farhat, Tuba; Rehman, Noor; ur Rehman, Mujeeb (Journal of Ayub Medical College Abbottabad, 2023)
Background: EDTA-dependent pseudo thrombocytopenia (EDTA-PTCP) refers to a falsely low platelet count occurring in the presence of ethylene diamine tetra-acetic acid (EDTA) anticoagulant during blood sample collection, which results in the formation of platelet clumps in vitro. This phenomenon has significant clinical implications, including unnecessary administration of platelets. Our study aims to evaluate the efficacy of sodium citrate anticoagulant for the resolution of EDTA-PTCP. Methods: This retrospective study was conducted in the haematology laboratory of Shifa International Hospital (SIH), Pakistan. Patients with pseudo thrombocytopenia (i.e. platelet count less than 150,000/ul with platelet clumps seen on peripheral smear) were included in this study if they had blood samples drawn in both EDTA and sodium citrate tubes less than 48 hours apart. Data was analyzed using IBM® SPSS Software Version 22. Results: A total of 151 study participants were included in this study. The mean age was 48.95±20.69 years and the majority were female (52.3%). Wilcoxon signed-rank test showed that there was a statistically significant difference in platelet count measured in both tubes (Z = -3.223, p=0.001). Overall, blood samples processed in sodium citrate tubes showed lower platelet count than EDTA samples. Sodium citrate anticoagulant was able to correct EDTA-PTCP in 47 (31.1%) of the cases. Conclusion: Sodium citrate anticoagulant was only able to resolve one-third of our EDTA-PTCP cases. Our findings do not support the use of sodium citrate as a suitable alternative for correction of EDTA-PTCP. ated.